Facilis portable air conditioner / Nornajiha Najla Md Isa ...[et al.] - Md Isa, Nornajiha Najla; Mohamad Halimin, Nurul Fatini; Arifin, Nurul Huda; Jumpaan, Sitinadia; Zakaria, Umi Sarah (2019)
At This Stage, A Detail Study About Facilis Portable Air Conditioner For Our New Product Development Was Done. It Is Necessary In Order To Get Detailed Information About The Product, Non-Verbal Interview And Research On The Innovation Product Based And Its Features, Quality, And Conveniences. Furthermore, The Theory Of The New Product Development Was Related To Our Product Concept. The Details Of Our Product Were Divided Into Research And Development, Product Design, Features, Concept Testing, Build Prototype And Test Marketing. In Research And Development, The Details Explanation Of How The Idea Generation And Market Survey Was Conducted. The Idea Actually Was Generated Based On The Difficulties For The Travelers And Recreational Clubs To Carry The Portable Air Conditioner Because The Limited Space In Bags And Also The Structure Or Shape Of The Portable Air Conditioner That Too Large. It Is Also Influenced By The Electricity Consumption Of The Existing Product That Is Overused That Affect The Electricity Cost. Next, The Details Study Based On Target Market For Our Product Is Electrical Store And Supermarket Which Is The Attractive Sport For The People That Like To Travel And Camping. From The Idea Generation And Market Survey Done, The Consumer Trend Canvas Was Completed. From That, It Shows The Summary Of The Product Detail, Analysis And Also Target Market On How Our Product Idea Was Develop. The Things That Was Analyzed Is The Product Design Or Features. At This Part, A Sketch Of Our Product Design Was Done Based On Combination Of Existing Product In Market. Concept Testing Is The Further Analysis Of The Product On How Target Market Will Accept The Innovation Product.